A cross-sectional study on caregivers' perspective of the quality of life and adherence of paediatric HIV patients to highly active antiretroviral therapy - Michael Lahai; Peter Bai James; Noel Nen'man Wannang; Haja Ramatulai Wurie; Sorie Conteh; Abdulai Jawo Bah; Mohamed Samai (BMC, 2020)
Abstract Background Poor compliance to highly active antiretroviral therapy (HAART) can result in the poor quality of life in children living with Human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS) because of low plasma drug concentration and the possibility of drug resistance. This study evaluates the response of caregivers for determination of adherence and the four quality of life domains in children (aged 14 years and under) on HAART. Methods We conducted a cross-sectional study of 188 children, each accompanied by their caregivers at Ola During Children's Hospital and Makeni Government Hospital between September and November 2016. Adherence to HAART and Quality of life was assessed using the WHO Quality of life summary questionnaire (WHOQOL-BREF). We obtained ethical approval from the Sierra Leone Ethics and Scientific Review Committee. Results The study revealed 5.9% adherence amongst paediatric patients, and a strong association of adherent patients(p = 0.019*) to the physical health domain (mean = 64.61 SD = 8.1). Caregiver HIV status showed a strong association with the physical (mean = 58.3, SD = 11.7 and p = 0.024*), and psychological health domains (mean = 68.2, SD = 14.7 and p = 0.001). Caregiver type (mother/father/sibling) accompanying child to hospital also showed strong associated with the physical (mean = 58.0, SD = 10.6, p <  0.001), psychological (mean 68.2 SD = 14.81 p <  0.001) and environmental health domains (mean = 59.7, SD = 13.47, p <  0.001). Further regression analysis showed a strong association with physical health domain for HIV positive caregivers (p = 0.014) and adherent paediatric patients (p = 0.005). Nuclear family also showed a strong association with psychological (p <  0.001) and environmental (p = 0.001) health domains. Conclusion This study showed a strong association between the quality of life domains and the involvement of nuclear family caregiver, HIV-positive caregiver and adherence to HAART. Our study suggests that the involvement of any member of the nuclear family, HIV positive parents and patient adherence to therapy can improve the quality of life of paediatric HIV/AIDS patients on highly active antiretroviral therapy in the two hospitals.